Sharing the Burden of Hybrid Threats: Lessons from the Economics of Alliances. Issue 2 (17th February 2023) - Balcaen, Pieter; Du Bois, Cind; Buts, Caroline
ABSTRACT: This article discusses the effects of the changing (hybrid) conflict environment on the burden sharing debate. We discuss the actions taken by both the alliance as the member states in repelling these threats, arguing that this mainly produces security outputs that are private or impure public. As the burden sharing literature currently lacks notions of hybrid threats, we believe the current modelling to be ill-suited to provide reliable assessments of member states' burden sharing behaviour. We address this void by adjusting the Joint Product Model, extending a country's security activities to a more inclusive 'whole of government (WoG) approach'. We depart from this WoG model to stress the challenges associated with comparing the contributions of member states in countering these threats. This leads us to dispute the use of aggregate military expenditures as a main variable to measure a country's degree of free riding. More and other types of (non-military) variables and proxy-indexes should be taken into account. The same remark goes for estimating the benefit-burden concordance within this framework of permanent non-linear state competition.